The Role of Interferons in Inflammation and Inflammasome Activation - Kopitar-Jerala, Nataša (Frontiers in Immunology, 2017)
Inflammation is an essential physiological process which enables survival during infection and maintains tissue homeostasis. Interferons and pro- and anti- inflammatory cytokines are crutial for appropriate response to pathogens, damaged cells or irritants in inflamamtory response. The inflammasom is multiprotein complex which initiates cleavage of pro-inflammatory cytokines IL-1β and IL-18 into active forms. In addition, inflammasomes initiate pyroptotic cell death. In the present review I summarize and analyze recent findings regarding the crosstalk of interferons and inflammasomes.